Association Between School Policies and Built Environment, and Youth's Participation in Various Types of Physical Activities. (July 2015) - Ward, Stephanie; Bélanger, Mathieu; Donovan, Denise; Caissie, Isabelle; Goguen, Julie; Vanasse, Allain
ABSTRACT BACKGROUND School environmental characteristics may be associated with youth's participation in different types of physical activities (PAs). This study aimed to identify which school policies and built environmental characteristics were associated with participation in organized, nonorganized, individual, and group‐based activities. METHODS This cross‐sectional analysis included 776 students in grade 5 or 6 from 16 schools. The school environment was assessed through school‐based questionnaires completed by school representatives. Types of PA and attainment of PA recommendations were obtained using self‐administered student questionnaires. Associations between environment and student PA were examined using multilevel logistic regressions. RESULTS Schools with favorable active commuting environments were positively associated with girls' participation in organized (odds ratio [OR] = 1.34, confidence interval [CI] = 1.04–1.74) and group‐based PA (OR = 1.54, CI = 1.19–1.99) and with boys' odds of participating in individual activities (OR = 1.45, CI = 1.04–2.04). There was also a positive relationship between having a school environment favorable to active commuting and boys' odds of meeting PA recommendations (OR = 2.19, CI = 1.43–3.37). School policies supporting PA were positively associated with girls' odds of participating in nonorganized activities (OR = 1.18, CI = 1.00–1.40). CONCLUSIONS School environments that favor active commuting may encourage participation in different types of PA. School policies promoting PA also may encourage girls to participate in organized activities.